PENERAPAN MODEL KOOPERATIF TIPE GROUP INVESTIGATION DENGAN MEDIA BENDA KONKRET DALAM PENINGKATAN PEMBELAJARAN BANGUN RUANG - Baeti Nurrokhmah; Joharman Joharman; Moh Salimi (Universitas Muhammadiyah Purwokerto, 2022)
The aims of this research are to describe the step in application of group investigation cooperative learning model using concrete media, to improve mathematics learning about geometry, and to find out problems and solutions. This research is a collaborative classroom action research (CAR) conducted in three cycles consisting of planning, action, observation, and reflection on each cycle. Subject of this research were 24 students. Source of data were obtained from students, teachers, and document. The techniques of collecting data were test, observation, and interview. The validity of the data applied source triangulation techniques and data triangulation techniques. The technique of analyzing data used qualitative technique, namely data reduction, data presentation, and drawing conclusion. The results of research showed that (1) the steps in application of Group Investigation cooperative learning model concrete media were: (a) delivery of the topic, (b) the establishment of the group, (c) identification of topics learning,(d) planning cooperation, (e) the implementation of the investigations, (f) the presentation of the investigation results,  and (f) evaluation; (2) the application of Group Investigation cooperative learning model using concrete media can improve mathematics learning about geometry from 66,67% in the first cycle, 83,34% in the second cycle, and increased by 91,67% in the third cycle; and (3) the problems faced in this research namely implementation of investigations and discussions was not effective and the lack of confidence of students at the time of presentation. The solution is students are given guidance and a clear time limit at the time of investigation or discussion, and students are given motivation to be confidence and familiarized to make presentation.